Microstructure and wear resistance of high-carbon pearlitic CrMo wear-resistant cast steels containing submicron-sized precipitates - Long Zhao; Haining Liu; Yu Song; Ganchao Zhai; Xiangru Chen; Qijie Zhai (Journal of Materials Research and Technology)
Vanadium (V) plays a crucial role in the formation of precipitates. In this study, different amounts of submicron-sized precipitates were introduced in high-carbon pearlitic CrMo wear-resistant cast steel by the addition of V. The result shows that the microstructure of high-carbon CrMo wear-resistant cast steel consists of lamellar pearlite and submicron-sized precipitates. With higher V content, the density of submicron-sized precipitates increases. The wear resistance of the steel also enhances with the addition of V, which is primarily attributed to the formation of submicron-sized precipitates resulting in the enhancement of initial mechanical properties and the creation of a harder work-hardening layer in worn surface. The wear mechanisms involve microploughing, microcutting, microfatigue, and microcracking in high-carbon pearlitic CrMo wear-resistant cast steel, but the introduction of submicron-sized precipitates leads to a substantial reduction in the depth of microploughing and microcutting.